SOCIAL AND ETHNO-EDUCATIONAL BASIS OF THE FORMATION OF THE NATIONAL CULTURES OF THE TURKISH PEOPLE (Scientific journal of the Fergana State University, 2024)
The article created guarantees of gender equality in the new Uzbekistan, this issue rose to the level of state policy, and our country took a progressive step in the field of human rights, increasing the socio-political activity of women in our country, protecting their health, supporting their aspirations and initiatives , providing them decent work and it is believed that special attention is paid to creating living conditions.